THE DEVELOPMENT OF READING SKILLS IN THAI LANGUAGE USING ACTIVITY-BASED LEARNING WITH TAI TECHNIQUE OF PHATOMSUKSA 3 STUDENTS IN PHRANAKHON SI AYUTTHAYA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Khaoluang , Supanee; Chobthamdee, Boriboon (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research were 1) to study in Thai reading skill by using activity-based learning with TAI technique of grade 3 students 2) to compare learning achievement before and after learning by activity-based learning with TAI technique 3) to study the satisfaction of learning activities in activity-based learning with TAI technique. The research samples were consisted of 12 students in grade 3 form Wat Hua Wiang School. Research instruments in this research were activity-based learning with TAI technique lesson plans, Thai reading skill assessment form and learning achievement tests. The statistics used for data analysis were Means, Standard Deviation and t-test. The results of the research found that 1) Thai reading skill of the students who studied by using activity-based learning with T.A.I techniques tended to be higher at a statistical significance of .05. 2) learning achievement after learning by using activity-based learning management with T.A.I techniques was higher than before learning at statistical significance. 3) the satisfaction of the students after learning by using activity-based learning management with T.A.I techniques was at the highest level.